Analysis of pneumonitis and esophageal injury after stereotactic body radiation therapy for ultra-central lung tumors. (September 2020) - Wang, Chunyu; Rimner, Andreas; Gelblum, Daphna Y.; Dick-Godfrey, Rosalind; McKnight, Dominique; Torres, Danielle; Flynn, Jessica; Zhang, Zhigang; Sidiqi, Baho; Jackson, Andrew; Yorke, Ellen; Wu, Abraham J.
Highlights: SBRT for ultra-central lung tumors can lead to severe pulmonary and esophageal toxicity. There was a 24 % rate of radiation pneumonitis, and a 5% rate of fatal pneumonitis. Severe esophageal toxicity including tracheo-esophageal fistula was observed. Multiplew metrics of lung and esophageal dose correlate with pulmonary and esophageal complications, respectively. Abstract: Objectives: SBRT has been associated with serious toxicity in ultra-central lung tumors, but little is known about the incidence and dosimetric correlates of pulmonary and esophageal complications in this setting. Materials and methods: We retrospectively reviewed SBRT patients whose lung tumor abutted proximal airways, or whose planning target volume overlapped esophagus. All patients received 5–15 fractions of high-dose, image-guided radiation. The primary endpoint was SBRT-related toxicity, with local control and survival as secondary endpoints. Results: We included 88 patients. Nineteen patients (22 %) experienced grade ≥3 (G3+) toxicity, including 6 cases of G3+ radiation pneumonitis and 4 cases of G3+ esophageal injury. Two patients developed trachea-esophageal fistula. Overall incidence of radiation pneumonitis was 23 %. Ten patients (11.4 %) succumbed to SBRT-related complications. Multiple dosimetric parameters for lung (including mean lung dose and V20Gy ) and esophagus (including maximum point dose) correlated with radiation pneumonitis and esophageal toxicity, respectively. No impact of fractionation on toxicity was seen. Conclusion: This analysis indicates that high rate and multiple manifestations of pulmonary and esophageal toxicity occur after SBRT for ultra-central tumors. In particular, severe radiation pneumonitis and tracheoesophageal fistula are possible. Dosimetric parameters such as mean lung dose and maximum esophageal dose are significantly correlated with toxicity. Further study is needed to optimize the safe delivery of SBRT in these patients.